Akap1 Regulates Vascular Function and Endothelial Cells Behavior. Issue 3 (March 2018) - Schiattarella, Gabriele Giacomo; Cattaneo, Fabio; Carrizzo, Albino; Paolillo, Roberta; Boccella, Nicola; Ambrosio, Mariateresa; Damato, Antonio; Pironti, Gianluigi; Franzone, Anna; Russo, Giusi; Magliulo, Fabio; Pirozzi, Marinella; et al.
Abstract : MitoAKAPs (mitochondrial A kinase anchoring proteins), encoded by the Akap1 gene, regulate multiple cellular processes governing mitochondrial homeostasis and cell viability. Although mitochondrial alterations have been associated to endothelial dysfunction, the role of mitoAKAPs in the vasculature is currently unknown. To test this, postischemic neovascularization, vascular function, and arterial blood pressure were analyzed in Akap1 knockout mice ( Akap1 −/− ) and their wild-type (wt) littermates. Primary cultures of aortic endothelial cells (ECs) were also obtained from Akap1 −/− and wt mice, and ECs migration, proliferation, survival, and capillary-like network formation were analyzed under different experimental conditions. After femoral artery ligation, Akap1 −/− mice displayed impaired blood flow and functional recovery, reduced skeletal muscle capillary density, and Akt phosphorylation compared with wt mice. In Akap1 −/− ECs, a significant enhancement of hypoxia-induced mitophagy, mitochondrial dysfunction, reactive oxygen species production, and apoptosis were observed. Consistently, capillary-like network formation, migration, proliferation, and AKT phosphorylation were reduced in Akap1 −/− ECs. Alterations in Akap1 −/− ECs behavior were also confirmed in Akap1 −/− mice, which exhibited a selective reduction in acetylcholine-induced vasorelaxation in mesenteric arteries and a mild but significant increase in arterial blood pressure levels compared with wt. Finally, overexpression of a constitutively active Akt mutant restored vascular reactivity and ECs function in Akap1 −/− conditions. These results demonstrate the important role of mitoAKAPs in the modulation of multiple ECs functions in vivo and in vitro, suggesting that mitochondria-dependent regulation of ECs might represent a novel therapeutic approach in cardiovascular diseases characterized by endothelial dysfunction. Abstract : Supplemental Digital Content is available in the text.